The Voice of Labour: A Life in Toronto's Construction Industry - Toppan, Marino; Principe, Angelo; Breda, Paola; Frank Iacobucci Centre for Italian Canadian Studies (Frank Iacobucci Centre for Italian Canadian Studies monograph series., 2019)
The memoirs of union organizer Marino Toppan, during the union organizing days of the residential construction "jungle" in Toronto: 1955-1980.